2013
DOI: 10.1371/currents.md.e246cf493a7edb1669f42fb735936b46
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dantrolene Therapy on Disease Phenotype in Dystrophin Deficient mdx Mice

Abstract: Dystrophin deficiency causes contraction-induced injury and damage to the muscle fiber, resulting in sustained increase in intracellular calcium levels, activation of calcium-dependent proteases and cell death. It is known that the Ryanodine receptor (RyR1) on the sarcoplasmic reticular (SR) membrane controls calcium release. Dantrolene, an FDA approved skeletal muscle relaxant, inhibits the release of calcium from the SR during excitation-contraction and suppresses uncontrolled calcium release by directly act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…In keeping with a previous report, mdx treatment with 40 mg/kg dantrolene alone lowers CK to some extent but not to the same degree as treatment with dantrolene and e23AON combined. 31 However, the high degree of rescue induced by each dantrolene and phosphorodiamidate morpholino oligomer (PMO) alone precludes distinguishing between a synergistic versus additive effect.
Figure 7 Creatine Kinase Reduction Is Boosted with Dantrolene/e23AON Combination Therapy (A) A reduction in creatine kinase levels with the addition of dantrolene in mice receiving 0, 10, and 50 mg/kg e23AON/dantrolene combination.
…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In keeping with a previous report, mdx treatment with 40 mg/kg dantrolene alone lowers CK to some extent but not to the same degree as treatment with dantrolene and e23AON combined. 31 However, the high degree of rescue induced by each dantrolene and phosphorodiamidate morpholino oligomer (PMO) alone precludes distinguishing between a synergistic versus additive effect.
Figure 7 Creatine Kinase Reduction Is Boosted with Dantrolene/e23AON Combination Therapy (A) A reduction in creatine kinase levels with the addition of dantrolene in mice receiving 0, 10, and 50 mg/kg e23AON/dantrolene combination.
…”
Section: Resultsmentioning
confidence: 99%
“…We demonstrated reduced CK levels in mdx mice treated with dantrolene alone, but observed no effect on any other measures of mdx histopathology or exon skipping in the absence of e23AON, consistent with published data. 31 , 60 In one published study in mdx mice, 6-week 40 mg/kg dantrolene treatment reduced both CK levels and some, but not all, measures of strength, despite no observed effect on histopathology. 31 It is reasonable to anticipate that if there is a beneficial effect in humans, chronic administration will be necessary.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, treatment with S107, which inhibits Ca 2+ leakage from the SR by reducing the deletion of calstabin from the RyR, alleviates muscle weakness and the dystrophic phenotype. In relation to these results, treatment with nifedipine or dantrolene, an inhibitor of DHPR or the RyR, alleviates the phenotype of dystrophic muscle 77,78) . Furthermore, the overexpression of sarcoplasmic reticulum Ca 2+ ATPase1 (SERCA1), which is responsible for Ca 2+ uptake into the SR in ÎŽ-sarcoglycan-null mice, resulted in attenuation of the dystrophic phenotype 79) .…”
Section: Role Of Ca 2+ Signaling In Muscle Atrophymentioning
confidence: 97%
“…The screening performed by Kendall and colleagues using the BioMol library has led to the identification of a number of active compounds [ 80 ]. Among those, Dantrolene, a drug approved by the Food and Drug Administration (FDA), was selected as the lead compound despite not having the highest efficacy among the molecules identified, due to clinical studies conducted on DMD patients and animals models for DMD that showed modest, although detectable, improvements in muscle pathology [ 105 , 106 , 107 ]. Dantrolene is a muscle relaxant known to inhibit excitation–contraction coupling in muscle, likely through its binding to the ryanodine receptor (RyR1) and by preventing the release of calcium from the sarcoplasmic reticulum.…”
Section: Hts Of Small Molecules That Enhance Skipping Of the Dystrmentioning
confidence: 99%